2013
DOI: 10.5433/1679-0359.2013v34n3p1381
|View full text |Cite
|
Sign up to set email alerts
|

Complexo enzimático na dieta de alevinos de kinguio (Carassius auratus)

Abstract: ResumoObjetivando avaliar a suplementação de complexo enzimático em dietas de alevinos de kinguios (Carassius auratus), foram utilizados 240 peixes com peso inicial de 1,36 ± 0,02g, distribuídos aleatoriamente, em 20 tanques de 150L, em quatro tratamentos e cinco repetições, com 12 peixes em cada unidade experimental. Os peixes foram arraçoados as 8h, 11h, 14h e 17h, com dietas contendo diferentes níveis de inclusão (0; 0,033; 0,066 e 0,099%) de complexo enzimático (amilase, protease, celulase, lipase, b-gluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…As observed, the data found in the literature are controversial. Such a divergence in results may be related to the level of inclusion of the enzymes in the diets, the structure of the enzymes present in the ingredients, the type of diet (live food and diets), the different types of enzymatic products, the different temperatures used in the formulation of the diet, the various species, as well as the ability of each species to adapt its digestive tract to the ingredient or their food preference, resulting in differences in the zootechnical performances and intestinal villi of the animals (Leenhouwers, Ter Veld, Verreth, & Schrama, 2007;Signor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed, the data found in the literature are controversial. Such a divergence in results may be related to the level of inclusion of the enzymes in the diets, the structure of the enzymes present in the ingredients, the type of diet (live food and diets), the different types of enzymatic products, the different temperatures used in the formulation of the diet, the various species, as well as the ability of each species to adapt its digestive tract to the ingredient or their food preference, resulting in differences in the zootechnical performances and intestinal villi of the animals (Leenhouwers, Ter Veld, Verreth, & Schrama, 2007;Signor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The use of digestive enzyme supplementation has been a common practice in poultry and pig feeding (Bedford, 2000), but in fish, this technique is not widely applied due to technological difficulties during pelletizing and extrusion processes, which involves high temperature levels and low stability to heat of enzymes (Mascarell & Ryan, 1997). Although several studies have demonstrated that the addition of exogenous digestive enzymes in the diet did not affect the survival and growth of several fish such as European sea bass larvae (Dicentrarchus labrax), juveniles of Nile tilapia (Oreochromis niloticus) (Signor et al, 2010), kinguio (Carium auratus) (Signor et al, 2013) and common carp (Cyprinus carpio) (Kazerani & Shahsavani, 2011), other studies have found positive results. Soares, Pereira Filho, Roubach, and Silva (2008) reported that the inclusion of exogenous protease in pelletized diets of tucunaré (Cichla sp.)…”
mentioning
confidence: 99%
“…Os ingredientes foram triturados, pesados, misturados (misturador "Y" USIBRAS®), sendo as enzimas adicionadas, em substituição ao inerte. O processo para obtenção da ração farelada seguiu a metodologia descrita por Signor et al (2013), posteriormente, as rações passaram pelo processo de peletização onde foi utilizanda a peletizadora CHAVANTE®. Todas as rações peletizadas permaneceram armazenadas sobre refrigeração durante todo o período experimental.…”
Section: Introductionunclassified
“…Para o peixe ornamental kiguio (Carassius auratus), a suplementação das rações com complexo enzimático (amilase, protease, celulase, lipase, βglucanase e fitase), não foi eficiente em influenciar diferenças significativas para parâmetros de desempenho, como o comprimento total (Signor et al, 2013).…”
Section: Resultsunclassified